Li trapping in nanolayers of cation 'disordered' rock salt cathodes. Issue 34 (22nd August 2022) - Diaz-Lopez, Maria; Chater, Philip A.; Proux, Olivier; Joly, Yves; Hazemann, Jean-Louis; Bordet, Pierre; Pralong, Valerie
Abstract : Cation rearrangement during cycling of a Li1.1 Mn0.7 Ti0.2 O2 cathode with a disordered rock-salt structure forms in situ a short-range ordered superstructure changing the connectivity of Li-migration channels and the electrochemical performance. Abstract : Disordered rock salt (DRS) cathodes have attracted considerable attention because of their high first charge capacities and relatively low cost. Here we investigate operando the structure and charge evolution of the Li1.1 Mn0.7 Ti0.2 O2 Li-excess rock salt cathode with a first charge capacity of 270 mA h g −1 . We associate a certain extent of the capacity fade in DRS to the in situ formation of locally ordered layered nanodomains during the electrochemical cycling of the long-range cation disordered rock salt. We quantify the short-range ordering of cations during cycling and evaluate its effect on the lithium-ion diffusion and charge compensation using operando studies based on X-ray total scattering and advanced spectroscopic methods at the Mn K-edge, namely high energy resolution fluorescence detected XANES and emission spectroscopies including main and valence-to-core transitions.